Implementasi Virtual Tour dalam Pengenalan Agrowisata pada Desa Ibru-Q dengan Menggunakan 3D Vista - Rizky Ardiansyah Putra, M.; Aldiansyah, Aldiansyah; Dwi Prakoso, Dimas; Arsa, Daniel (Green Publisher Indonesia, 2024)
Virtual tour is a technological innovation that provides an interactive experience in getting to know tourist destinations virtually. This study aims to implement a virtual tour in introducing Ibru-Q Village Agrotourism using 3d Vista. The potential of Agrotourism in Ibru-Q Village has great potential as a nature-based educational tourism destination. The methods used include data collection through field observations, interviews with managers, and visual documentation to build virtual tour content. The results of the study showed that the implementation of a virtual tour was able to increase tourist interest and provide more interesting and in-depth information about the potential of Ibru-Q Village Agrotourism, including plant diversity, agricultural methods, and the uniqueness of local culture. This virtual tour also facilitates the accessibility of information for prospective visitors who have not been able to visit the location in person. These findings indicate that virtual tour technology contributes positively to the promotion of tourist destinations, especially in the digital era.